2012
DOI: 10.1371/journal.pone.0049500
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Refines the Synthesis of Chloroplast Proteins in Maize (Zea mays) in Response to Drought and Light

Abstract: To better understand abscisic acid (ABA) regulation of the synthesis of chloroplast proteins in maize (Zea mays L.) in response to drought and light, we compared leaf proteome differences between maize ABA-deficient mutant vp5 and corresponding wild-type Vp5 green and etiolated seedlings exposed to drought stress. Proteins extracted from the leaves of Vp5 and vp5 seedlings were used for two-dimensional electrophoresis (2-DE) and subsequent matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…In maize roots, proteins associated with drought stress were primarily involved in energy and metabolism, redox homeostasis, and regulatory processes (Hu et al, 2011); in maize leaves, the identified proteins were primarily involved in processes such as ATP synthesis, protein synthesis, chlorophyll synthesis, CO 2 fixation, gluconeogenesis, antioxidant defense, and signal transduction. Most of the proteins that differentially accumulated in leaves were localized to the chloroplasts and functioned in an ABA-dependent manner in response to drought and light stress (Hu et al, 2012). These results reveal an important role of ABA in regulating the synthesis of drought-induced proteins.…”
Section: Figmentioning
confidence: 77%
See 1 more Smart Citation
“…In maize roots, proteins associated with drought stress were primarily involved in energy and metabolism, redox homeostasis, and regulatory processes (Hu et al, 2011); in maize leaves, the identified proteins were primarily involved in processes such as ATP synthesis, protein synthesis, chlorophyll synthesis, CO 2 fixation, gluconeogenesis, antioxidant defense, and signal transduction. Most of the proteins that differentially accumulated in leaves were localized to the chloroplasts and functioned in an ABA-dependent manner in response to drought and light stress (Hu et al, 2012). These results reveal an important role of ABA in regulating the synthesis of drought-induced proteins.…”
Section: Figmentioning
confidence: 77%
“…As determined by omics studies, the proteins involved in the maize drought response primarily include protective proteins (such as HSPs) (Benesova et al, 2012;Hu et al, 2010a;Li et al, 2009;Luo et al, 2010), late embryogenesisabundant proteins (LEAs) (Benesova et al, 2012;Huang et al, 2012), stress response-related proteins (such as NBS-LRR resistance-like protein) (Hu et al, 2012), 14-3-3-like proteins (Huang et al, 2012;Li et al, 2009), phytohormonerelated proteins, and signaling proteins (such as auxinrepressed protein and serine/threonine protein kinase) (Bonhomme et al, 2012;Hu et al, 2011;Luo et al, 2010).…”
Section: Figmentioning
confidence: 99%
“…This protein catalyses the ATP-dependent phosphorylation of ribulose-5-phosphate to ribulose-1,5-phosphate, a key step in the pentose phosphate pathway where carbon dioxide is assimilated. Some data showed that PRK synthesis could be regulated by such factors like light, drought stress or ABA (Hu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The spots were aseptically removed under a laminar flow hood. The processing of the gel plugs, trypsin digestion and MALDI-TOF-MS analysis using an Ettan MALDI-TOF Pro mass spectrometer (GE Healthcare, USA) was performed as previously described [16]. Mascot software (v2.2.03, http://www.matrixscience.com/) was used to automatically match the obtained MS/MS spectra to proteins in the NCBInr 20,121,026 databases (21,171,493 sequences; 7,255,144,311 residues; http://www.ncbi.nlm.nih.gov/).…”
Section: Mass Spectrometry and Protein Identificationmentioning
confidence: 99%